2014
DOI: 10.5301/jva.5000312
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Catheter Locking Solutions and the Prevention of Catheter Dysfunction: A Meta-Analysis

Abstract: Our results suggest that there is no substantial difference between heparin lock solutions versus all other types of catheter lock solutions for catheter dysfunction. Whether there are significant benefits of citrate or other novel lock solutions requires further robust studies. These findings have significant implications for future design of clinical trials in TDCs and the delivery of dialysis-related services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…Although there is increasing recognition that antibiotic lock solutions can reduce the risk of infection, the standard lock solutions used clinically remain PBS alone and PBS containing heparin as an anticoagulant agent (26). Heparin is a sulfated polysaccharide analogous to carrageenan, a sulfated polysaccharide that is isolated from marine algae and is used as a growth substrate in microbiology plates to culture bacteria (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing recognition that antibiotic lock solutions can reduce the risk of infection, the standard lock solutions used clinically remain PBS alone and PBS containing heparin as an anticoagulant agent (26). Heparin is a sulfated polysaccharide analogous to carrageenan, a sulfated polysaccharide that is isolated from marine algae and is used as a growth substrate in microbiology plates to culture bacteria (10).…”
Section: Discussionmentioning
confidence: 99%
“…These include sodium citrate at various concentrations, acid citrate dextrose formula A (ACD‐A), antibiotic solutions +/− sodium citrate, NS, various concentrations of heparin, and rt‐PA. In recent systematic reviews, the only solution that showed potential benefit over heparin in preventing CVC malfunction was rt‐PA …”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing recognition that antibiotic lock solutions can reduce the risk of infection, the standard lock solutions used clinically remain PBS alone or containing Heparin as an anti-coagulant agent Chapla et al . (29). Heparin is a sulfated polysaccharide analogous to carrageenan, also a sulfated polysaccharide that is isolated from marine algae and used as a growth substrate in microbiology plates to culture bacteria (10).…”
Section: Discussionmentioning
confidence: 99%